2016
DOI: 10.1371/journal.pone.0152662
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Differentially Methylated Amylin DNA as a Biomarker of β-Cell Loss in Type 1 Diabetes

Abstract: In type 1 diabetes (T1D), β-cell loss is silent during disease progression. Methylation-sensitive quantitative real-time PCR (qPCR) of β-cell-derived DNA in the blood can serve as a biomarker of β-cell death in T1D. Amylin is highly expressed by β-cells in the islet. Here we examined whether demethylated circulating free amylin DNA (cfDNA) may serve as a biomarker of β-cell death in T1D. β cells showed unique methylation patterns within the amylin coding region that were not observed with other tissues. The de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…So amylin level could be considered as important target for the regeneration of β cells and treatment of diabetes. This argument is based on the fact that increased amylin level is connected with the apoptosis of β cells [51]. However, CPP extract considerably reversed the serum amylin level in treated groups.…”
Section: Assessment Of Fasting Bloodmentioning
confidence: 99%
“…So amylin level could be considered as important target for the regeneration of β cells and treatment of diabetes. This argument is based on the fact that increased amylin level is connected with the apoptosis of β cells [51]. However, CPP extract considerably reversed the serum amylin level in treated groups.…”
Section: Assessment Of Fasting Bloodmentioning
confidence: 99%
“…The potential for other β-cell-specific genes (e.g., IAPP ) was recently demonstrated [38]. With emerging data on whole genome methylation sequencing, it should be possible to identify new, perhaps more specific, methylated and unmethylated CpGs in β-cells in an unbiased manner without consideration of gene expression patterns.…”
Section: Differentially Methylated Dna As a Biomarker Of β-Cell Stresmentioning
confidence: 99%
“…Studies were found increased levels of unmethylated preproinsulin DNA in peripheral blood samples of patients with new-onset T1DM compared with controls [37,38]. However, although this hypothesis has been disputed, circulating demethylated amylin DNA has seemed to be a valid biomarker for β-cell death in T1DM [39].…”
Section: Insulin Gene An D Its Epigenetic Modificationsmentioning
confidence: 99%